MIMIKRI PRIBUMI TERHADAP KOLONIALISME BELANDA DALAM NOVEL SITTI NURBAYA KARYA MARAH RUSLI (Kajian Postkolonialisme) - -, Hartono (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2005)
This study was conducted by using postcolonialism theory.This study of postcolonialism, focused on mimikri or indigene'simitation to Dutch colonials in Sitti Nurbaya novel by Marah Rusli,intended to uncover and describe some aspect of Dutch colonialismculture which they were imitated by indigene society. This study alsoattempt to describe fiction element that was used by writer to conveyimitation of Dutch colonialism culture.This study showed that ini the novel of Sitti Nurbaya byMarah Rusli was found mimikri to Dutch colonialism which wasexecuted by the characters. They are Sitti Nurbaya, Samsul Bahri,Datuk Maringgih, Arifm, and Bachtiar. Well, the Dutch colonialismculture that was imitated by them are (1) language, (2) feast andequipment of human life (clothes and weapon), (3) work system(trade), (4) artistry (art of music and art of movement), and (5)science. Fiction element that was used by writer to uncover thatmimikri realization is characterization element.Keywords: mimikri, postcolonialism